Glutathione S-Transferase Alpha 4 Prevents Dopamine Neurodegeneration in a Rat Alpha-Synuclein Model of Parkinson’s Disease - Jewett, Michael; Dickson, Elna; Brolin, Kajsa; Negrini, Matilde; Jimenez-Ferrer, Itzia; Swanberg, Maria (Frontiers in Neurology, 2018)
Parkinson’s disease (PD) is a common, progressive neurodegenerative disease, which typically presents itself with a range of motor symptoms, like resting tremor, bradykinesia, and rigidity, but also non-motor symptoms such as fatigue, constipation, and sleep disturbance. Neuropathologically, PD is characterized by loss of dopaminergic cells in the substantia nigra pars compacta (SNpc) and Lewy bodies, neuronal inclusions containing α-synuclein (α-syn). Mutations and copy number variations of SNCA, the gene encoding α-syn, are linked to familial PD and common SNCA gene variants are associated to idiopathic PD. Large-scale genome-wide association studies have identified risk variants across another 40 loci associated to idiopathic PD. These risk variants do not, however, explain all the genetic contribution to idiopathic PD. The rat Vra1 locus has been linked to neuroprotection after nerve- and brain injury in rats. Vra1 includes the glutathione S-transferase alpha 4 (Gsta4) gene, which encodes a protein involved in clearing lipid peroxidation by-products. The DA.VRA1 congenic rat strain, carrying PVG alleles in Vra1 on a DA strain background, was recently reported to express higher levels of Gsta4 transcripts and to display partial neuroprotection of SNpc dopaminergic neurons in a 6-hydroxydopamine (6-OHDA) induced model for PD. Since α-syn expression increases the risk for PD in a dose-dependent manner, we assessed the neuroprotective effects of Vra1 in an α-syn-induced PD model. Human wild-type α-syn was overexpressed by unilateral injections of the rAAV6-α-syn vector in the SNpc of DA and DA.VRA1 congenic rats. Gsta4 gene expression levels were significantly higher in the striatum and midbrain of DA.VRA1 compared to DA rats at 3 weeks post surgery, in both the ipsilateral and contralateral sides. At 8 weeks post surgery, DA.VRA1 rats suffered significantly lower fiber loss in the striatum and lower loss of dopaminergic neurons in the SNpc compared to DA. Immunofluorescent stainings showed co-expression of Gsta4 with Gfap at 8 weeks suggesting that astrocytic expression of Gsta4 underlies Vra1-mediated neuroprotection to α-syn induced pathology. This is the second PD model in which Vra1 is linked to protection of the nigrostriatal pathway, solidifying Gsta4 as a potential therapeutic target in PD.